Refractive Error Profile in a Tertiary Centre in Western Nepal
INTRODUCTION: Refractive error is one of the causes of avoidable blindness. Myopia, hypermetropia and astigmatism are the common types of refractive error. Not many studies are done to detect pattern of refractive error in Western Nepal. So, the study will determine the prevalence and distribution of refractive errors. MATERIALS AND METHODS: A prospective study of all consecutive patients of age less than 40 years who visited eye department, Gandaki Medical College, between May 2010 and May 2011 was conducted. Visual acuity, naked eye and pin hole examination was done by ophthalmic assistant with cycloplegic refraction when needed. Those who did not turn up for refraction were excluded from the study. RESULTS: A total of 601 patients were seen within the study period. Mean age of male patients was 22.4 years